Transcranial direct current stimulation (tDCS) combined with blindsight rehabilitation for the treatment of homonymous hemianopia: a report of two-cases - Perin, Cecilia; Viganò, Barbara; Matteo, Barbara Maria; Cornaggia, Cesare Maria; Cerri, Cesare Giuseppe; Meroni, Roberto (Journal of Physical Therapy Science, 2017)
[Purpose] Homonymous hemianopia is one of the most common symptoms following neurologic damage leading to impairments of functional abilities and activities of daily living. There are two main types of restorative rehabilitation in hemianopia: “border training” which involves exercising vision at the edge of the damaged visual field, and “blindsight training,” which is based on exercising the unconscious perceptual functions deep inside the blind hemifield. Only border effects have been shown to be facilitated by transcranial direct current stimulation (tDCS). This pilot study represents the first attempt to associate the modulatory effects of tDCS over the parieto-occipital cortex to blindsight treatment in the rehabilitation of the homonymous hemianopia. [Subjects and Methods] Patients TA and MR both had chronic hemianopia. TA underwent blindsight treatment which was combined with tDCS followed by blindsight training alone. MR underwent the two training rounds in reverse order. [Results] The patients showed better scores in clinical-instrumental, functional, and ecological assessments after tDCS combined with blindsight rehabilitation rather than rehabilitation alone. [Conclusion] In this two-case report parietal-occipital tDCS modulate the effects induced by blindsight treatment on hemianopia.